Answer:
Total charge
=
$
4.25
+
$
1.50
(
m
−
1
)
Total charge for 12 miles
=
$
20.75
Explanation:
Building the rule
The trick with algebra is to think what you would do with numbers, then substitute letters.
Mile number 1 costs
$
4.25
The rest of the miles
⇒
(
total miles
−
1
)
×
$
1.50
Putting this all together we have:
$
4.25
+
(
total miles
−
1
)
×
$
1.50
The question instructs that we are to use the letter m for the total miles so we now have:
$
4.25
+
(
m
−
1
)
×
$
1.50
This would be written as:
$
4.25
+
$
1.50
(
m
−
1
)
So
Total charge
=
$
4.25
+
$
1.50
(
m
−
1
)
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
Determine the charge for 12 miles
Total charge
=
$
4.25
+
$
1.50
(
12
−
1
)
Total charge
=
$
4.25
+
$
1.50
(
11
)
Total charge for 12 miles
=
$
4.25
+
$
16.50
=
$
20.75
Hope this helps you...
:)
The answer would be b-5+6
The common ratio of the sequence is calculated by dividing the second term by the first term or dividing the third term by the second term. That is,
r = 250 / 333 = 0.75
or r = 187 / 250 = 0.748 = 0.75
To get the next term, we multiply 187 by 0.75 giving us an answer of 140.25 or 141.
Answer: You can use only common factor (3).
Step-by-step explanation:
12g²-27h²
3 . ( 4g² - 9h² )